The effectiveness of memory rehabilitation following neurological disabilities: a qualitative inquiry of patient perspectives - das Nair, Roshan; Lincoln, Nadina (Routledge Open Select, 2013)
The evidence for the effectiveness of memory rehabilitation following neurological conditions, mainly studied through quantitative methodologies, has been equivocal. This study aimed to examine feedback from participants who had been through a randomised controlled trial (RCT) comparing two types of memory rehabilitation with a self-help control. It was envisaged that this information would offer a detailed understanding of patient experience of going through a trial and the perceived effects of having attended group sessions. Through 31 in-depth interviews, data collected were thematically analysed. The seven themes identified highlighted improvements in insight and awareness of memory problems and their neurological conditions, knowledge and skills about using memory aids; and as a consequence, improvements in cognitive functions, mood, and confidence, assertiveness and control over their condition. Participants also reported an altered perspective of life that helped them deal with their problems, and the therapeutic effects of attending group sessions. While these improvements were mainly reported in the intervention groups, even those in the control group reported some benefits. This study highlights that it is both feasible and advantageous to embed qualitative research within the traditional RCT methodology to arrive at a more nuanced understanding of patient experiences and intervention outcomes.